Slow Innovation in Europe’s Peripheral Regions: Innovation beyond Acceleration. - Mayer, Heike (Verl. der Österreichischen Akademie der Wissenschaften, 2020)
Innovation processes are often conceptualized with an urban bias and are therefore theorized solely considering the perspective of the urban environment (e.g. close face-to-face contacts, dense urban milieus, fast interactions between a multitude and diverse actors, etc.). As a result, innovation theories do not sufficiently consider the context of the periphery and how this context may foster or hinder the development of innovative products, technologies and services. In the meantime, economic geographers started to conceptualize innovation processes in peripheral locations as “slow innovation” and they have emphasized the need to consider innovative processes as more isolated, less dependent on frequent interactions with partners and more strategic in terms of seeking information and knowledge. Another stream of research that recently emerged, considers the periphery as a space in which creativity can more freely unfold because innovators are positioned at the fringes and are more free to experiment with unconventional ideas. Less emphasis has been placed on the notion that peripheral spaces can also offer opportunities for experimentation because they afford innovative actors the opportunity to reflect, search, experiment and advance in undisturbed, more “slow” ways, perhaps because they by choice are shielded from accelerating economic pressures. In this sense, the relative emptiness or thinness of the periphery can be considered not only as an asset for innovation, but also as an empowering characteristic for innovative behavior. This exploratory essay examines these processes through exploratory case studies of slow innovators in peripheral regions in the European Alps (Italy and Austria).

Die Autorin arbeitet die Besonderheiten von Innovation in peripheren Regionen in Österreich und Italien heraus.
Keywords: Regionalentwicklung; Ländlicher Raum; Periphere Region; Strukturschwacher Raum; Innovationsprozess; Geschwindigkeit; Verzögerung; Akteur; Exploration; Schlüsselakteur